Anxiety over EFL speaking and writing: A view from language classrooms - Gkonou, Christina (Studies in Second Language Learning and Teaching, 2011)
The assumption that foreign language learners experience a high level of anxiety mainly when faced with speaking activities implies that research should focus on those learners prone to anxiety over that skill. Despite not being widely investigated, foreign language writing anxiety also seems to be a concern for a large number of students. Drawing on questionnaire findings, the study reported in this article examined the nature of, and the connection between the English language classroom speaking and writing anxiety of 128 Greek EFL learners in private language school settings. Speaking anxiety was operationalised by Horwitz, Horwitz, and Copeʼs (1986) Foreign Language Classroom Anxiety Scale, and writing anxiety was measured by Gungle and Taylorʼs (1989) ESL version of the Daly and Millerʼs (1975) Writing Apprehension Test. Interconstruct and intraconstruct associations between the two instruments were examined through principal components analysis with varimax rotation and correlations check. A significant and high correlation was found between classroom anxiety and speaking anxiety, thus indicating that the English language classroom context is a source of speaking anxiety. Writing anxiety was found to load primarily on items relating to attitudes towards writing in English followed by self-derogation for the process and fear of negative evaluation by the teachers and/or by fellow students. On the basis of the findings, suggestions are made concerning the reassessment of the influence that writing anxiety exerts on classroom performance and the adoption of teaching techniques that promote topic-centred process writing.